Régulations en santé materno-infantile en milieu populaire à partir de la notion de risque - Alfonsina Faya-Robles (Anthropologie & Santé)
In Brazil, with every passing day public authorities have become more and more involved in the field of maternal and child heath, producing important changes in the behaviors and reproductive experiences of women. This investment has sparked an important change in regulation forms of birth and delivery, between a process of medicalization and healthicization. In that context, the evaluation and monitoring of risks have become fundamental and follow sanitary goals such as the reduction of child mortality, one of the « Millennium Development Goals » of the UN, which has become one of Brazil's priority. In health services, the epidemiological category of risk schedules the care of pregnancies by drawing the distinction between « high » and « low risk » pregnancies. However, this notion distinguishes pregnancies not only according to medical criteria but also to social criteria, conveying social representations and prejudices against pregnant women considered as « deviant ». Based on ethnographic research in the city of Recife in Brazil's Nordeste, this article proposes to examine the extension of the category of risk in the field of pregnancy management to the working class women. It reveals a shift from the normalization of pregnant women's bodies towards a normalization of parentality and maternity. The article concludes by putting the disciplinary force of the category of risk in perspective in order to show how it is subjectivized in women's experiences.